Study the electrical properties of ZnOSiO2 detector prepared by free rappid thermal oxidation - Abdul Majeed E. Ibrahim; Raid A.Isma'l; Wlla M. Mohammed (Tikrit Journal of Pure Science)
Zinc thin films deposited on (n-type)silicon at 510o C with oxidation times (10,20,30,35) sec have been oxidized. Zinc have been deposited by thermal diffusion method using heater instead of conventional furnace .It is found that we can get zinc oxide with outoxegen and closed farneces rapidly. The electrical properties in dark show that the detector is shottky diode, and the best time to obtain the detector is 35 sec, and the ideality factor is 3.3 with a work function of 0.58 ev. It is found that the resalts at light power (50,100,150,200,250) mw/cm2.Show that the detector oxidiced in 35 sec have detectivity factor 540.8 and have a high responsivity which enable the detector to detect the IR signals.